An Analysis of Metaphor in Korean Song Lyrics by Bangtan Soyeondan (BTS) - Putu Ayu Krisna Wulandari; I Wayan Mawa (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2022)
This study aims to analyze the form of metaphor used in BTS song lyrics. The subject of this research is BTS, and the object of this research is song lyrics. The method used in this research was a qualitative research method. The data was collected by means of observation and document record/note by listening, reading song lyrics and noting important parts of song lyrics. Research procedures: First, the researcher downloaded BTS songs and their lyrics on the internet. Second, the researcher listened to the song. Three, researcher translated Korean songs into English. Fourth, the researcher read the lyrics of the song, then the metaphorical forms found were marked. Then the researcher found out the types of metaphors and their meanings. Finally, the metaphorical forms used in the lyrics of BTS’songs were discussed and analyzed using the theory of Larson and Lakoff & Johnson. Based on the results of the analysis, there are 5 types of metaphorical forms found in the lyrics of BTS songs: (1) Dead metaphor (2) Active metaphor (3) Structural metaphor (4) Orientational metaphor (5) Ontological